Penanganan terhadap Anak Pelaku Tindak Pidana Penganiayaan yang Terlibat dalam Geng Motor di Wilayah Badung - Ria Putriliana Waskita; A.A Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2020)
A bike gang refers to a group of youths (teenagers) having the same school background in an area who are members of a two-wheeled motor vehicle user community. The criminal act of maltreatment committed by a group of biker gang in Bali has violated the provisions of the applicable criminal law. With regard to the fact, the urgency of the modus operandi of the criminal act of maltreatment committed by biker gang and the legal protection for young biker gang who commit crimes of maltreatment are examined in the present study. The method used in this research is the empirical method. The modus operandi appeared as the mode applied by criminals to commit criminal acts and the implementation of legal protection against bikers who committing the criminal act of maltreatment in the Badung District Police jurisdiction is through not overriding the children’s rights as child defendants, such as the right to legal assistance at every level of examination in line with procedures determined by law. It would be better if, in implementing criminal sanctions, law enforcers take the condition of the community, the perpetrators of crimes, into account in order to foster legal awareness within them.